The curious kid's science book : 100+ creative hands-on activities for ages 4-8 - Citro, Asia, ....- (Seattle : Innovation Press, 2015)
How would your child find the answers to these questions? In The Curious Kid's Science Book, your child will learn to design his or her own science investigations to determine the answers! Children will learn to ask their own scientific questions, discover value in failed experiments, and -- most importantly -- have a blast with science. The 100+ hands-on activities in the book use household items to playfully teach important science, technology, engineering, and math skills. Each creative activity includes age-appropriate explanations and (when possible) real life applications of the concepts covered. Adding science to your at-home schedule will make a positive impact on your child's learning. Just one experiment a week will help build children's confidence and excitement about the sciences, boost success in the classroom, and give them the tools to design and execute their own science fair projects.
Keywords: Knutselen